SOCIAL ATTITUDES TO MENTALLY RETARDED IN INTEGRATION CONTEXT - Vera Tejeiro, Ana (Anales de Psicología / Annals of Psychology)
It is very important to know the social attitudes towards mentally retarded people since their own self-esteem and the success of their mainstreaming depend and are closely related to these social attitudes.These are the results from the first year of an elementary state school in Madrid after carrying out a sociometric survey to know the normal children attitudes toward the mentally retarded children in a mainstreaming context. This sample consisted of 14 boys and girls; three of them were mentally retarded. This work is a part of a research trying to evaluate these attitudes to modify them when necessary.The data suggest that mentally retarded children are hardly chosen and very frequently rejected by their peers. As a group, mentally retarded subjects overestimate their social acceptance. In the actual integration there are other different reasons from the simply cognitive ones.